Taxation, corruption and the exchange rate regime - Carsten Hefeker (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
The paper analyzes the relation between institutional quality, such as corruption, in a country and its monetary regime. It is shown that a credibly …xed exchange rate to a low ination country, like a currency board, can reduce corruption and improve the …scal system. A monetary union, however, has ambiguous eects. I …nd that that there is convergence between countries with regard to the level of corruption.
Keywords: D72; E63; F33; 330; Exchange Rate Regime; Monetary Policy; Fiscal Policy; Seigniorage; Corruption; Developing and Transition Countries